Surgical rectus sheath block versus laparoscopic bilateral dual transversus abdominis plane block after minimally invasive colorectal cancer surgery: randomized clinical trial of impact on recovery - Takeharu Kato; Shunsuke Tsukamoto; Yuri Oishi; Gen Tomizawa; Yudai Kumamoto; Kohei Takura; Hiroshi Nagata; Yasuyuki Takamizawa; Tetsufumi Sato; Yukihide Kanemitsu (British Journal of Surgery, 2026)
Abstract Background Effective multimodal analgesia is essential after minimally invasive colorectal surgery. This randomized trial evaluated whether adding surgeon-performed surgical rectus sheath block (SRSB) or laparoscopic bilateral dual transversus abdominis plane (BD-TAP) block to intravenous patient-controlled analgesia (IV-PCA) improved postoperative quality of recovery. Methods This single-centre, three-arm superiority trial randomized adults undergoing minimally invasive colorectal resection (1 : 1 : 1) by stratified block allocation at a Japanese cancer centre. Patients and outcome assessors were blinded. The primary outcome was the Japanese version of the 15-item Quality of Recovery questionnaire (QoR-15) score 24 h after arrival in the postanaesthesia care unit. Missing postoperative QoR-15 item responses were handled using multiple imputation, and treatment effects were estimated using ANCOVA adjusted for the four randomization stratification factors. Each primary comparison used a Bonferroni-adjusted one-sided significance level of 0.025. Secondary outcomes included the 48-h QoR-15 score, postoperative pain scores, time to first rescue analgesia, and cumulative consumption of analgesics and antiemetics over 48 h. Results Between July 2024 and December 2025, 320 patients were randomized (control, 110; SRSB, 107; and BD-TAP block, 103); 309 were analysed (105, 103, and 101 respectively). Compared with control, BD-TAP block resulted in a higher 24-h QoR-15 score (adjusted mean difference 10.44 (95% c.i. 3.06 to 17.83) points; one-sided P = 0.003), whereas superiority of SRSB was not demonstrated (adjusted mean difference 5.50 (95% c.i. −1.88 to 12.89) points; one-sided P = 0.072). At 48 h, the adjusted mean difference for BD-TAP block versus control was 8.01 (95% c.i. 0.18 to 15.83) points (two-sided P = 0.045), an exploratory finding unadjusted for multiplicity. The median time to first rescue analgesia was longer with SRSB (27.8 h) and BD-TAP block (25.3 h) than control (3.3 h), but cumulative 48-h fentanyl consumption and length of hospital stay did not differ significantly. No block-related complications were observed. Conclusion BD-TAP block resulted in better 24-h recovery than IV-PCA alone. Superiority of SRSB was not demonstrated. Registration number jRCT1031240153 (Japan Registry of Clinical Trials).